The Doppelgänger phenomenon and death: a peculiar case of homicide by a subject with first-episode psychosis - Cristiano Barbieri; Gabriele Rocca; Caterina Bosco; Lucia Tattoli; Ignazio Grattagliano; Giancarlo Di Vella (Oxford University Press, 2022)
The Doppelgänger phenomenon refers to the experience of a direct encounter with one's self, characteriswed by: (i) the perception of a figure with one's own identical physical features; or (ii) the apprehension that the perceived figure shares the same personality and identity. The Doppelgänger does not only look like the same person, it is his/her double. The perceptual element is usually a hallucination, although occasionally a false perception of an actual figure may be involved. This phenomenon has been described in individuals suffering from overwhelming fear, severe anxiety or intoxication, epilepsy, as well as in the sleep-wakefulness transition. It has also been reported in major psychoses. The fear of imminent death often precedes the Doppelgänger experience. This report presents the case of a 30-year-old man, Mr. Y, who was stabbed to death by Mr. X, his "double". The aggressor and his victim, although not related, were truly doubles; remarkably, they shared the same name and surname, age, professional activity and place of work. Moreover, they attended the same sports center but barely knew each other. The forensic psychiatric evaluations in Mr. X, subsequent to the crime committed, were suggestive of a psychotic condition. This case is unique in the scientific literature. In the most serious psychotic forms, the issue of the "double" calls into question not only the dissociative processes involved in the etiopathogenesis of the disorder, but also bio-psycho-social elements, as well as personal data in this case, which made the victim and the aggressor "identical". In the context of psychopathological functioning, the delusional mood (Wahnstimmung) that precedes the development of delirium is a sort of gateway to an impending psychotic illness, involving delusional awareness or mood (atmosphere). In psychosis, splitting is the main issue and this influence is seen as an evil, foreign, apocalyptic and unknown side no longer recognised as belonging to the self even in a physical sense. In such a situation, it is felt that the only way to survive is by suppressing one's double as a defense against disorganisation of the self.